Predicting Cardiovascular Risk in People With Diabetic Retinopathy : Study Using Framingham Risk Score - Harahap, Vicia Belladona Carolina; Metita, Mirza; Dewi, Nadia Artha (Majalah Oftalmologi Indonesia, 2023)
Introduction: People with type 2 diabetes have an increase risk of cardiovascular disease (CVD). Framingham risk score is used to determine 10 years the risk of CVD in asymptomatic patients for primary prevention. Up to now, there have been no similar studies regarding the risk of CVD in diabetic retinopathy (DR) patients in Indonesia. Therefore, we would like to investigate the corelation between DR and CVD risk through the population using Framingham risk score. Methods: This research is a Population-Based Cross-sectional Study. The data was taken from the villages in Malang Regency. Participant with diabetes aged > 40 was recruited. The available data was then processed according to the variables and assessed using Framingham Risk Score. The scores were classified as high, intermediate, and low risk. Results: From 953 samples there were 155 respondents with Diabetes Mellitus (DM), 23 of them experience DR. There were more female participants than men in DM group without DR (73.9%) and DR group (73.9%). A significant correlation between diabetic retinopathy and CVD risk was found (r=0.407, p=0.001). The risk of CVD in 10 years is low in diabetic patients without retinopathy ( p=0.001), but in patients with diabetic retinopathy, the risk of CVD in 10 years is intermediate-high (p=0.001). Conclusion: There is corelation between Diabetic Retinopathy and risk for cardiovascular disease in intermediate-high category using Framingham risk score.